The Use of Constructivist Learning Theory in Ki Hadjar Dewantara System Through Tut Wuri Handayani in Merdeka Curriculum - Nalle, Christina; Saryanto, Saryanto; Rejokirono, Rejokirono (Malikussaleh University, Aceh, Indonesia, 2025)
This study presents an overview of Ki Hajar Dewantara's constructivism learning theory as interpreted through the system that gave rise to Tut Wuri Handayani. The system places students as the center of the learning process, while the role of the teacher is that of a guide who provides flexibility for children to develop their potential, creativity, talents, and interests according to their nature. Students are not entirely free to seek information and knowledge. Still, guidance from teachers and parents dramatically aids in identifying the nature and form of knowledge children require based on their developmental stage. This aligns with the constructivism learning theory, which suggests that teachers serve as facilitators, motivators, and communicators for their students. This study employs a qualitative approach, analyzing data from literature through an interpretive process to comprehend and provide context for the gathered qualitative data. This study will reveal how Ki Hajar Dewantara's constructivism learning theory compares to other systems. What is the relevance of Ki Hajar Dewantara's constructivism learning theory in the Merdeka Curriculum? The study's results lead to the following conclusions: First, the constructivism learning theory in Ki Hajar Dewantara's system emphasizes the importance of students' Independence in their thinking, the role of teachers as agents of change, the role of teachers as motivators, facilitators, and communicators for students, and the importance of Tut Wuri Handayani. Second, Tut Wuri Handayani illustrates Ki Hajar Dewantara's views on the Merdeka Curriculum through the roles of teachers and students in schools.